Six months in a Syrian monastery : being the record of a visit to the head quarters of the Syrian church in Mesopotamia, with some account of the Yazidis or devil worshippers of Mosul and Al Jilwah, their sacred book. - Parry, Oswald H. [Hutton]. (New Jersey)
xviii, 400 s.